Renal insufficiency, mortality, and drug management in heart transplant. Results of the CARIN study. (26th June 2014) - Janus, Nicolas; Launay‐Vacher, Vincent; Sebbag, Laurent; Despins, Philippe; Epailly, Eric; Pavie, Alain; Obadia, Jean‐François; Pattier, Sabine; Varnous, Shaïda; Pezzella, Veronica; Trillaud, Laurence; Deray, Gilbert; et al.
Summary Renal insufficiency (RI) is a frequent complication in heart transplant (HT) patients. The main objectives of the Cardiac trAnsplantation and Renal INsufficiency (CARIN) study were to follow the evolution of renal function after heart transplantation (HTx), to identify the factors associated with the decline of renal function, to describe the impact of RI on mortality during 3 years after the HT, and to observe the renal profile of the prescriptions. CARIN was a French retrospective, multicentric, study. Data were collected for patients who received a HT between 2000 and 2005. Data collection was performed at five time points: before HTx (T0), 1(T1), 6(T6), 12 (T12), and 36 (T36) months after HTx. Glomerular filtration rate (GFR) was estimated with aMDRD formula. RI was defined as GFR < 60 ml/min/1.73 m². Four hundred and forty‐one patients from five HT centers were included. The prevalences of RI were 28.8% (T0), 54.0% (T1), 50.4% (T6), 51.6% (T12), and 59.6% (T36). Age and cyclosporine were independently linked to the decline of renal function. Hypertension and GFR < 60 at T0 were independent risk factors of mortality. 48.7–64.7% of the nonimmunosuppressive prescriptions were drugs that required dosage adjustment in RI patients or for which no data were available concerning administration in RI patients. RI is highly frequent after HTx. Because RI is a risk factor of mortality, any sparing renal strategies have to be undertaken.